The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Changes in stream food‐web structure across a gradient of acid mine drainage increase local community stability - Justin P. F. Pomeranz; Jeff S. Wesner; Jon S. Harding (Ecology, 2020)
Understanding what makes food webs stable has long been a goal of ecologists. Topological structure and the distribution and magnitude of interaction strengths in food webs have been shown to confer important stabilizing properties. However, our understanding of how variable species interactions affect food‐web structure and stability is still in its infancy. Anthropogenic stress, such as acid mine drainage, is likely to place severe limitations on the food‐web structures availabe, due to changes in community composition and body mass distributions. Here, we used mechanistic models to infer food‐web structure and quantify stability in streams across a gradient of acid mine drainage. Multiple food webs were iterated for each community based on species pairwise interaction probabilities, in order to incorporate the variability of realistic food‐web structure. We found that food‐web structure was altered systematically with a 32‐fold decrease in the number of links and a twofold increase in connectance across the gradient. Stability generally increased sixfold with increasing acid mine drainage stress, regardless of how interaction strengths were estimated. However, the distribution of the stability measure, s , for some impacted communities separated into clusters of higher and lower magnitude depending on how interaction strengths were estimated. Management and restoration of impacted sites needs to consider their increased stability, as this may have important implications for the recolonization of desirable species. Furthermore, active species introductions may be required to overcome the internal ecological inertia of affected communities.

Faecal indicator bacteria in New Zealand freshwater fish: a pilot study - Sarah Coxon; Jon S Harding; Brent Gilpin (New Zealand Journal of Marine and Freshwater Research, 2019)
Recent studies have suggested that poikilothermic animals, such as fish, may represent a previously overlooked source of the faecal indicator bacteria (FIB) used for the assessment of water quality. However, quantitative studies of FIB in poikilotherms are scarce. We investigated the presence of FIB in the faeces of five freshwater fish species. E. coli and enterococci were detected in 71 and 76% of faecal samples, respectively. Concentrations were highly variable, with maximum concentrations (2.1 × 10 4 E. coli and 1.3 × 10 6 enterococci per gram of faecal material) up to four orders of magnitude higher than present in the water column. FIB were not detected in faecal samples from marine fish. Our findings suggest that FIB ingested from the environment may be capable of replication within the fish gut, making fish a potential source and transport mechanism for FIB in New Zealand freshwaters. This may have implications for water quality monitoring.

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Invasive Nitrogen-Fixing Plant Amplifies Terrestrial–Aquatic Nutrient Flow and Alters Ecosystem Function - Simon D. Stewart; Megan B. Young; Jon S. Harding; Travis W. Horton (Ecosystems, 2019)

Acute toxicity of arsenic to larvae of four New Zealand freshwater insect taxa - Olivier Champeau; Jo Anne E. Cavanagh; Thomas J. Sheehan; Louis A. Tremblay; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2017)
Arsenic, often found in gold deposits, can enter aquatic systems. The toxicity of arsenate (As(V)), the most common valence state of arsenic in freshwater, was assessed on the larvae of four freshwater insect taxa from naturally acidic (pH 5.9) and circumneutral (pH 7.4) New Zealand streams. Insects from the acidic stream were more sensitive to arsenate‐spiked water than those from the circumneutral stream. Early instars ( Deleatidium spp. (Leptophlebiidae) were the most sensitive compared to later instars (3–6 mm) (4‐d LC 50 1.5 and 3.5 mg/L, respectively) or to the stonefly Zelandobius spp. (Gripopterygidae) (4‐d LC 50 2.5 mg/L). The cased caddisflies Pycnocentria spp. (Conoesucidae) and Helicopsyche spp. (Helicopsychidae) from circumneutral stream were the most tolerant (4‐d LC 50 45.4 and 113 mg/L, respectively). The 14‐day arsenic LC 10 and LC 50 for Deleatidium spp. late instars exposed to mining‐impacted water were 0.12 and 0.36 mg/L, respectively.

Production of phosphatase and extracellular stalks as adaptations to phosphorus limitation in Didymosphenia geminata (Bacillariophyceae) - Jon Bray; Jon O’Brien; Jon S. Harding (Hydrobiologia, 2017)

Disentangling the stream community impacts of Didymosphenia geminata: How are higher trophic levels affected? - Phillip G. Jellyman; Jon S. Harding (Biological Invasions, 2016)

Identifying Catchment-Scale Predictors of Coal Mining Impacts on New Zealand Stream Communities - Joanne E. Clapcott; Eric O. Goodwin; Jon S. Harding (Environmental Management, 2016)

Physicochemical predictors of the invasive diatom Didymosphenia geminata at multiple spatial scales in New Zealand rivers - Jonathan Bray; Jon S. Harding; Cathy Kilroy; Paul Broady; Philippe Gerbeaux (Aquatic Ecology, 2016)

A Geoenvironmental Model for Orogenic Gold Deposits to Predict Potential Environmental Effects - Dave Craw; Jo Cavanagh; Joanna Druzbicka; Jon S. Harding; Gemma Kerr; James Pope; Dave Trumm (Mine Water and the Environment, 2015)

Stream biomonitoring using macroinvertebrates around the globe: a comparison of large-scale programs - Daniel F. Buss; Daren M. Carlisle; Tae-Soo Chon; Joseph Culp; Jon S. Harding; Hanneke E. Keizer-Vlek; Wayne A. Robinson; Stephanie Strachan; Christa Thirion; Robert M. Hughes (Environmental Monitoring and Assessment, 2015)

Leaf breakdown, detrital resources, and food webs in streams affected by mine drainage - Kristy L. Hogsden; Jon S. Harding (Hydrobiologia, 2013)

Diatom community response to an acid mine drainage gradient - Kate A. Schowe; Jon S. Harding; Paul A. Broady (Hydrobiologia, 2013)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Metal contamination in aquatic environments: science and lateral management. By Samuel N.Luoma and Philip S.Rainbow. Published in 2008 by Cambridge University Press, Cambridge, United Kingdom (www.cambridge.org). 573 p, hardcover. ISBN 978–0‐521–86057–4. Price au$200.00. - Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2009)

Persistence of a significant population of rare Canterbury mudfish ( Neochanna burrowsius ) in a hydrologically isolated catchment - Jon S. Harding; David A. Norton; Angus R. McIntosh (New Zealand Journal of Marine and Freshwater Research, 2007)
Canterbury mudfish ( Neochanna burrowsius ) are endemic to a small region of Canterbury, South Island, New Zealand and classified as nationally endangered. We reviewed data from the New Zealand Freshwater Fish Database and trapped fish in July 2006, and January and February 2007 in the Waianiwaniwa Valley, Canterbury to determine the importance of this catchment for mudfish conservation. Mudfish were found in 19 of the 28 sites sampled. Waianiwaniwa Valley sites accounted for 47% of all Canterbury mudfish database records of mean catch per unit effort (CPUE) ≥6 fish. The population comprised young recruits ( 120mm TL) indicating a healthy population. Drying of the lower mainstem, and low dissolved oxygen levels in summer create a unique catchment free of larger predatory fish and with reduced competition from other fish species. We estimated that mudfish occur in at least 24.3 km of the Waianiwaniwa River, making this catchment the most important refuge known for the conservation of this species.

Spatial biodiversity patterns in a large New Zealand braided river - Duncan Gray; Mike R. Scarsbrook; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2006)
At the catchment scale, braided rivers are recognised as physically unstable, dynamic landscapes, yet at finer spatial scales they are a mosaic of micro‐habitats including physically unstable braided channels and more stable spring‐sources, spring creeks, and groundwater zones. We investigated benthic invertebrate communities at 103 sites in braided channels, springs and hillslope streams in the Waimakariri River, New Zealand over 3 months. One hundred taxa were identified, including a number of rare phreatic species. Highest total taxonomic richness occurred in springs (81 taxa), whereas main braids and hillslope streams had fewer taxa (54 and 56, respectively). Spring‐fed habitats also had the highest diversity of unique taxa (22), whereas main channels had five and hillslope streams 11 taxa, respectively. Several taxa including the mayfly Deleatidium and orthoclad chironomids were ubiquitous, whereas others such as the flatworm Prorhynchus had restricted habitats. Our results highlight the high spatial heterogeneity of braided river habitats and the importance of springs as centres of invertebrate diversity within braided river catchments.

Can forest fragments reset physical and water quality conditions in agricultural catchments and act as refugia for forest stream invertebrates? - Jon S. Harding; Koen Claassen; Niels Evers (Hydrobiologia, 2006)

Longitudinal patterns in benthic communities in an urban stream under restoration - Tanya J. Blakely; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2005)
Okeover Stream, on the University of Canterbury campus in Christchurch, New Zealand, has been the subject of restoration efforts since 1998. Our study focused on quantifying the response of this urban stream to current restoration efforts. Initially, physico‐chemical conditions and biological communities at three sites along the Okeover Stream were compared with three physically similar sites on each of nearby Waimairi Stream and Avon River. General physical and chemical parameters were similar in all streams with circum‐neutral pH, specific conductivity ranging from 167 to 173 μS/cm, dissolved oxygen ranging from 9.0 to 9.2 mg/litre, low turbidity, and similar hydrological conditions. However, analysis of heavy metals in the sediment showed mean lead (Pb) concentrations in Okeover and Waimairi Streams exceeded ANZECC ISQG‐low trigger values (86.9 and 83.7 mg/kg, respectively), whereas Avon River sediment Pb levels (27.3 mg/ kg) were below trigger values. Benthic taxonomic richness did not differ significantly among the three streams. However, Okeover Stream community was dominated by the amphipod Paracalliopefluviatilis, whereas in Waimairi Stream and Avon River the gastropod snails Potamopyrgus antipodarum and Physella acuta were the dominant benthic fauna. A further assessment made at six sites along 1200 m of Okeover Stream showed no distinct longitudinal patterns in physical or chemical conditions, but there was a strong pattern in benthic macroinvertebrate communities. Taxonomic richness and caddisfly diversity increased downstream, with twice as many taxa at the most downstream site than the uppermost sampling site. In upper reaches, copper (Cu), Pb, and zinc (Zn) concentrations in sediments all exceeded ANZECC ISQG‐low trigger values. Despite ongoing restoration efforts in Okeover Stream, sedimentation, the presence of high heavy metal concentrations, intermittent flows in headwaters, and possible barriers to adult recolonisation seem to be having a continuing negative impact on benthic communities, especially in the headwaters.

Historic deforestation and the fate of endemic invertebrate species in streams - Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2003)
Deforestation is a global phenomenon threatening the biodiversity of many unique forested ecosystems. The volcanic calderas of Banks Peninsula, New Zealand, experienced widespread deforestation from 1860 to 1900 when >98% of the indigenous forest was removed. Streams on the Peninsula possess several regionally‐endemic species. The objective of this study was to assess the effect of historic deforestation on stream faunas by surveying the distribution of endemic and other benthic invertebrate species in relation to remnant and regenerating indigenous forest fragments. Twenty‐seven sites, in nine catchments were surveyed. Three catchments were dominated by forest, three by farmland, and three were predominantly farmland with forested headwaters. Taxonomic richness was significantly greater in forested streams than agricultural streams, particularly for Ephemeroptera, Plecoptera, and Trichoptera taxa. Distributions of the regionally‐endemic hydrobiosid caddisflies Costachorema peninsulae and Edpercivalia banksiensis were restricted to forest fragments. Two other endemics, the stonefly Zelandobius wardi and the caddisfly Hydrobiosis styx , were rarely collected but seemed to be restricted to headwater sites in forest. In contrast, the blepharicerid Neocurupira chiltoni was widely distributed in streams, regardless of land cover, and in relative abundances unrelated to site location within the catchment. Evidence from Banks Peninsula streams suggests that throughout New Zealand a number of species unknown to science may have been lost because of past deforestation, and that remnant forested habitats may be vital to the conservation and preservation of regionally endemic species.

Strategies for coexistence in two species of New Zealand Hydropsychidae (Trichoptera) - Jon S. Harding (Hydrobiologia, 1997)